ANALISIS KEKUATAN LAPANGAN SEBAGAI STRATEGI DALAM PENINGKATAN DAYA SAING SATUAN PENDIDIKAN - Fajariah, Putri; Sohiron, Sohiron (STKIP Pesisir Selatan, 2026)
Global competition in the field of education requires every educational institution to possess effective strategies for improving quality, relevance, and competitiveness. However, many educational institutions in Indonesia still face challenges in systematically identifying and optimizing their internal potential, causing quality development programs to operate below expectations. Based on this issue, this study aims to analyze the role of field strength analysis as a managerial strategy to enhance the competitiveness of educational institutions. This research employs a qualitative approach using the library research method, focusing on conceptual exploration and the review of previous studies. Data were collected from various sources, including books, national and international scientific journals, research reports, and educational policy documents. The data were analyzed using the content analysis technique, which involved stages of data reduction, thematic classification, interpretation of interrelated variables, and drawing theoretical conclusions. The findings reveal that the implementation of field strength analysis plays a significant role in strengthening institutional competitiveness through improving strategic planning effectiveness, optimizing internal resources, enhancing institutional image and identity, and developing innovative programs based on local potential. Moreover, this approach serves as an essential instrument in establishing a sustainable, participatory, and innovation-oriented quality management system.